2013
DOI: 10.1371/journal.ppat.1003142
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus Effector Proteins Suppress Inflammasome Activation by Interfering with Host Autophagy Signaling

Abstract: Bacterial pathogens utilize pore-forming toxins or sophisticated secretion systems to establish infection in hosts. Recognition of these toxins or secretion system by nucleotide-binding oligomerization domain leucine-rich repeat proteins (NLRs) triggers the assembly of inflammasomes, the multiprotein complexes necessary for caspase-1 activation and the maturation of inflammatory cytokines such as IL-1β or IL-18. Here we demonstrate that both the NLRP3 and NLRC4 inflammasomes are activated by thermostable direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 46 publications
(66 reference statements)
3
74
0
Order By: Relevance
“…Woolery and others [96] showed that VopS also inhibits the activation of pro-inflammatory and cell survival signaling pathways, such as NFkB and the mitogen-activated protein kinases JNK and Erk. In corroboration with these findings supporting a role for VopS in subversion of pro-inflammatory immune responses, VopS (and also VopQ) was shown to suppress inflammasome assembly as a result of bacterial activation of the nucleotide-binding oligomerization domain receptors (NOD-like receptors or NLRs) [97]. AMPylation of Rho GTPases was shown to disrupt their interaction with IAPs (inhibitors of apoptosis proteins), which mediate GTPase targeted degradation.…”
Section: Vopssupporting
confidence: 56%
See 1 more Smart Citation
“…Woolery and others [96] showed that VopS also inhibits the activation of pro-inflammatory and cell survival signaling pathways, such as NFkB and the mitogen-activated protein kinases JNK and Erk. In corroboration with these findings supporting a role for VopS in subversion of pro-inflammatory immune responses, VopS (and also VopQ) was shown to suppress inflammasome assembly as a result of bacterial activation of the nucleotide-binding oligomerization domain receptors (NOD-like receptors or NLRs) [97]. AMPylation of Rho GTPases was shown to disrupt their interaction with IAPs (inhibitors of apoptosis proteins), which mediate GTPase targeted degradation.…”
Section: Vopssupporting
confidence: 56%
“…Consistent with a role for T3SS2 during enteric infections, Gotoh Table 8.2). It is interesting to note that four of these effectors target actin polymerization, either directly or indirectly: VopL (VPA1370) and VopV (VPA1357) bind actin to cause F-actin nucleation and bundling, respectively [65,97]; VopC (VPA1321) and the recently characterized VopO (VPA1329) act upstream of actin and target small Rho GTPases and the RhoA guanine nucleotide exchange factor (GEF) GEF-H1 [101]. While VopA (VPA1346) inhibits MKKs, VopZ (VPA1336) blocks TAK1 (transforming growth factor-β (TGF-β)-activated kinase 1, MAPK37), both of which prevent MAPK pathway signaling [102,103].…”
Section: T3ss2mentioning
confidence: 99%
“…This phenotype has obvious implications for an infected host, but its drastic nature likely masked other important cellular consequences. In support of this, VopS has previously been shown to reduce cytokine production during infection through an unknown mechanism (15).…”
mentioning
confidence: 89%
“…10 A previous study of inflammasome activation by the pathogen Vibrio parahaemolyticus suggested that a bacterial effector, VopQ, inhibited NLRC4 inflammasome activation by inducing autophagic degradation, but the mechanism was not determined. 16 We have recently found in an in vivo model of Pseudomonas aeruginosa infection in mice that autophagy downregulates inflammasome activation by this microbe. 17 We set out therefore to examine in more detail the influence of autophagy on the activation of the NLRC4 inflammasome by the T3SS of P. aeruginosa, which produces a rapid activation of the NLRC4 inflammasome by a mechanism that is entirely dependent on its T3SS.…”
Section: Introductionmentioning
confidence: 99%